An Empirical Analysis of the Influential Factors of RMB Cross-border Settlement in the Process of RMB Internationalisation - Zhang, Cong (2018)
While Chinese economy is the second largest in the world, the international status of the Chinese currency renminbi (RMB) is not in line with it. The outbreak of the financial crisis showed the drawbacks of the international monetary system. Under such circumstance, RMB internationalization becomes inevitable. As the first step of RMB internationalisation, the RMB settlement of cross-border trade was introduced in July 2009. It is practically significant to understand its development status, analyse the problems of the development, and study the factors influencing its development. Based on the existing literature, this dissertation theoretically analysed the factors influencing the scale of RMB cross-border settlement. After the unit root test, cointegration test and Granger causality test, the VAR model was established. Through the impulse response analysis and variance decomposition, the influencing factors on cross-border trade RMB settlement were studied. The conclusion was that the RMB exchange rate fluctuations, offshore RMB market and China's trade scale had different effects on the scale of RMB settlement of cross-border trade. Moreover, it was found that RMB exchange rate volatility exerted the greatest impact. Finally, the dissertation, based on the theoretical discussion and empirical study, proposed relevant countermeasures and suggestions for promoting the development of RMB cross-border settlement in three aspects, maintenance of the stability of the RMB, promotion of the development of offshore RMB market and improvement of competitiveness of foreign trade products.